A toolkit for Assessing Fiscal Vulnerabilities and Risks in Advanced Economies - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper ;, 2012)
This paper presents a range of tools and indicators for analyzing fiscal vulnerabilities and risks for advanced economies. The analysis covers key short-, medium- and long-term dimensions. Short-term pressures are captured by assessing (i) gross funding needs, (ii) market perceptions of default risk, and (iii) stress dependence among sovereigns. Medium- and long-term pressures are summarized by (iv) medium- and long-term budgetary adjustment needs, (v) susceptibility of debt projections to growth and interest rate shocks, and (vi) stochastic risks to medium-term debt dynamics. Aiming to cover a wide range of advanced economies and minimize data lags, has also influenced the selection of empirical methods. Due to these features, they can, for example, help inform the joint IMF-FSB Early Warning Exercise (EWE) on the fiscal dimensions of economic risks.